Pouk književnosti v poklicnih šolah v Sloveniji - Krakar-Vogel, Boža (Jezik in slovstvo, 2001)
The paper outlines the difference in teaching literature in three-year vocational school before and after the national curricular renovation. The new curricula, textbooks and teaching methods are better adapted to the abilities and interests of students-readers in these schools, while keeping literature an autonomous academic domain with a number of teaching aims related to nature of the course. The new reform of vocation education currently underway, which will reduce the course, will lower these standards adapted student's abilities and needs.
Keywords: didactic method; didaktika; pouk književnosti; srednje šole; strokovne šole